In vivo evaluation of anticancer efficacy of drug loaded cockle shell‐derived aragonite nanoparticles - Fu, Wenliang; P Rameli, Mohd Adha; Tengku Ibrahim, Tengku Azmi; Mohd Noor, Mohd Hezmee; Mohamad Yusof, Loqman; Abu Bakar @ Zakaria, Md Zuki (John Wiley & Sons, 2019)
Doxorubicin (DOX) is an effective and commonly used anthracycline anticancer drug for the treatment of osteosarcoma (OS). However, its antitumor effect is hampered by the nonspecific distribution and significant adverse effects. Nanoparticles based drug delivery systems are promising approaches to maximize the anticancer efficacy while decrease the side effects. In this study, biogenic aragonite nanoparticles (ANPs) were developed from cockle shells and loaded with DOX. An orthotopic rat OS model was induced by UMR‐106 cells tibia cavity injection. The anticancer efficacy study included five groups: normal control group, OS model group, free DOX group (2 mg/kg), DOX‐ANPs 1 group (2 mg of equivalent DOX/kg) and DOX‐ANPs 2 group (1.5 mg of equivalent DOX/kg). This study demonstrates that the DOX‐ANPs treatment groups can significantly reduce the tumor volume and increase the surviving ratio as compared to the OS model group. In addition, these two DOX‐ANPs groups showed less toxicity to the normal organs compared to the free DOX group. Furthermore, DOX‐ANPs 2 group showed the similar anticancer efficacy as DOX‐ANPs 1 group, which suggested that DOX loaded onto the ANPs may allow the reduction of chemotherapy doses. These results highlight the promising application of ANPs derived from cockle shells as an effective drug delivery system for a successful chemotherapy against OS.